Cover Picture: Aldo‐X Bifunctional Building Blocks for the Synthesis of Heterocycles (The Chemical Record 2/2017). Issue 2 (February 2017) - Unknown
Abstract : The cover picture shows the versatile uses of aldo‐X bifunctional building blocks in the synthesis of heterocyclic compounds, which are a class of organic molecules that contains at least an aldehyde or acetal group in the structure. See the Personal Account by P. Ravichandiran, B. Lai and Y. Gu (DOI:10.1002/tcr.201600042 ).